2021
DOI: 10.1108/ijlss-07-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability excellence: the interactions of lean production, internal green practices and green product innovation

Abstract: Purpose This study aims to investigate the interactions between lean production, internal green practices, green product innovation and sustainable performance metrics. The study further looks at the mediation effect of internal green practices and green product innovation between lean production and sustainable performance dimensions. Design/methodology/approach The questionnaire was used to glean data from 209 manufacturing firms. All the hypothesized relationships were processed by using partial least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 73 publications
3
30
0
Order By: Relevance
“…GI has an excellent reputation in developing ES and EP. However, green product innovation has only a significant effect on financial performance [65]. Chu et al's [66] findings demonstrate that the GI is a meaningful analyst of financial performance.…”
Section: Gi Es and Epmentioning
confidence: 99%
See 1 more Smart Citation
“…GI has an excellent reputation in developing ES and EP. However, green product innovation has only a significant effect on financial performance [65]. Chu et al's [66] findings demonstrate that the GI is a meaningful analyst of financial performance.…”
Section: Gi Es and Epmentioning
confidence: 99%
“…green corporate culture impacts indirectly on a firm's green performance. Afum et al's [65] findings show that green practices have an indirect effect on sustainable performance and financial performance. Similarly, GI mediates the association between sustainable corporate performance and the knowledge management process [5].…”
Section: Mediating Effect Of Gimentioning
confidence: 99%
“…Some scholars (Henao et al, 2019;Mies and Gold, 2021) contend that the social implications of LM and CPS have only been peripherally studied; hence call for more studies. The works of Afum et al (2021) and Jabbour et al (2020) point out that empirical studies regarding the social consequences of LM and CPS is vital and needed from emerging economies due to the unexpected outcomes in such highly complex settings. Responding to this call, our study examines the impact of LM and CPS on social reputation (SR).…”
Section: Lean Management and Circular Production 1213mentioning
confidence: 99%
“…More studies from the African context are needed because the results obtained from developed economies may simply not reflect the findings that could be obtained from emerging countries. Afum et al (2021) and Kwarteng et al (2021) have explicitly suggested that there is literature deficiency to direct the actions of managers on the lean and circularity themes, despite their burgeoning stages in the Ghanaian context. Consequently, undertaking this study in the Ghanaian context can be a valuable milestone for practitioners and industrial consortium.…”
Section: Lean Management and Circular Production 1213mentioning
confidence: 99%
See 1 more Smart Citation